Comparison of Four‐Dimensional Magnetic Resonance Imaging Analysis of Left Ventricular Fluid Dynamics and Energetics in Ischemic and Restrictive Cardiomyopathies. Issue 4 (24th January 2022) - Riva, Alessandra; Sturla, Francesco; Pica, Silvia; Camporeale, Antonia; Tondi, Lara; Saitta, Simone; Caimi, Alessandro; Giese, Daniel; Palladini, Giovanni; Milani, Paolo; Castelvecchio, Serenella; Menicanti, Lorenzo; et al.
Abstract : Background: Time‐resolved three‐directional velocity‐encoded (4D flow) magnetic resonance imaging (MRI) enables the quantification of left ventricular (LV) intracavitary fluid dynamics and energetics, providing mechanistic insight into LV dysfunctions. Before becoming a support to diagnosis and patient stratification, this analysis should prove capable of discriminating between clearly different LV derangements. Purpose: To investigate the potential of 4D flow in identifying fluid dynamic and energetics derangements in ischemic and restrictive LV cardiomyopathies. Study Type: Prospective observational study. Population: Ten patients with post‐ischemic cardiomyopathy (ICM), 10 patients with cardiac light‐chain cardiac amyloidosis (AL‐CA), and 10 healthy controls were included. Field Strength/Sequence: 1.5 T/balanced steady‐state free precession cine and 4D flow sequences. Assessment: Flow was divided into four components: direct flow (DF), retained inflow, delayed ejection flow, and residual volume (RV). Demographics, LV morphology, flow components, global and regional energetics (volume‐normalized kinetic energy [KEV ] and viscous energy loss [ELV ]), and pressure‐derived hemodynamic force (HDF) were compared between the three groups. Statistical Tests: Intergroup differences in flow components were tested by one‐way analysis of variance (ANOVA); differences in energetic variables and peak HDF were tested by two‐way ANOVA. A P ‐value of <0.05 was considered significant. Results: ICM patients exhibited the following statistically significant alterations vs. controls: reduced KEV, mostly in the basal region, in systole (−44%) and in diastole (−37%); altered flow components, with reduced DF (−33%) and increased RV (+26%); and reduced basal–apical HDF component on average by 63% at peak systole. AL‐CA patients exhibited the following alterations vs. controls: significantly reduced KEV at the E‐wave peak in the basal segment (−34%); albeit nonstatistically significant, increased peaks and altered time‐course of the HDF basal–apical component in diastole and slightly reduced HDF components in systole. Data Conclusion: The analysis of multiple 4D flow‐derived parameters highlighted fluid dynamic alterations associated with systolic and diastolic dysfunctions in ICM and AL‐CA patients, respectively. Level of Evidence: 2 Technical Efficacy Stage: 3